(untitled) (Kinesiology, 2023)
Measurement of the time spent in sleep, sedentary behaviour, and physical activity across the full 24-h day (i.e. 24-h movement behaviours) is essential for time-use research among adolescents. However, self-reported questionnaires for the assessment of 24-h movement behaviours are scarce. The aim of this study was to examine the validity and reliability of recently developed Daily Activity Behaviours Questionnaire (DABQ) for the assessment of time spent in sleep, sedentary behaviour, light physical activity, and moderate-to-vigorous physical activity among adolescents. A convenience sample of 59 high-school students (34 female, age range: 15–18 years) was recruited. Participants were asked to complete a web-based DABQ at two occasions (two-weeks apart) to examine test-retest reliability of the DABQ, and to wear activPAL accelerometer to examine convergent validity of the DABQ. The test-retest reliability correlation coefficients (ICC) for the durations of sleep, sedentary behaviour, light physical activity, and moderate-to-vigorous physical activity were 0.49, 0.64, 0.51, and 0.66, respectively. Convergent validity correlation coefficients (Spearman’s ρ) were 0.51, 0.38, 0.25, and 0.53, respectively. Our findings are comparable with the reliability and validity of most existing sleep, sedentary behaviour, or physical activity questionnaires among adolescents. However, DABQ is one of the first validated questionnaires that resonates with the emerging 24-h movement paradigm. The observed reliability and validity are indicating satisfactory measurement properties of the DABQ to be used in time-use research among adolescents. Keywords: time-use questionnaire, time-use composition, physical behaviours, time-use epidemiology